A Qualitative Study of the Barriers and Opportunities for Adoption of Web-Portals for Doctors and Patients in Russia; Journal of Medical Systems; Vol. 41, iss. 4 - Kopanitsa G. D. Georgy Dmitrievich (2017, 2017)
Title screen